(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The Insolvency Act contains a preconcursal mediatorial figure, the court procedure of payments, which allows citizens and legal persons, whether or not employers, to agree an agreement that allows the viability of personal and professional activity. This rule includes many specialties for the mediation process and even allows the transformation of the role of mediator into administrator, creating a hybrid figure appropriate for the specific context of bankruptcy.